The resilient power of CSR: Sustained risk reduction despite widespread ESG adoption - Merladet Artiach, Jorge; Lumbreras Sancho, Sara; Ramos Galán, Andrés (My University, 2025)
This paper explores the role of CSR in risk mitigation within an increasingly ESG-focused environment. Using monthly data from 2016 to 2023, we employ several risk measures representing systematic, idiosyncratic and downside risks. Through comprehensive panel regression analysis, we reveal robust risk reduction effects across model specifications, contrasting with the mixed profitability outcomes reported in the literature. Notably, the risk mitigation effect is broad-based and intensifies as ESG adoption becomes widespread, challenging prevailing assumptions of diminishing impact. These results have significant implications for firm valuation and investor decision making.

This paper explores the role of CSR in risk mitigation within an increasingly ESG-focused environment. Using monthly data from 2016 to 2023, we employ several risk measures representing systematic, idiosyncratic and downside risks. Through comprehensive panel regression analysis, we reveal robust risk reduction effects across model specifications, contrasting with the mixed profitability outcomes reported in the literature. Notably, the risk mitigation effect is broad-based and intensifies as ESG adoption becomes widespread, challenging prevailing assumptions of diminishing impact. These results have significant implications for firm valuation and investor decision making.
Artículos en revistas
Keywords: Instituto de Investigación Tecnológica (IIT)